Hydrogel/enzyme dots as adaptable tool for non-compartmentalized multi-enzymatic reactions in microfluidic devices - Simon, David; Obst, Franziska; Haefner, Sebastian; Heroldt, Toni; Peiter, Martin; Simon, Frank; Richter, Andreas; Voit, Brigitte; Appelhans, Dietmar (Reaction Chemistry & Engineering, 2019)
This study presents a simple method to integrate hydrogel/enzyme dots for the performance of multi-enzymatic reactions in two microfluidic devices and shows the conversion of enzyme educts under continuous flow as well as the reusability of the hydrogel/enzyme dots in microfluidic devices. For this purpose, five different enzymes were physically entrapped in a hydrogel matrix composed of poly(ethylene glycol) diacrylate, 2-(dimethylamino)ethyl methacrylate, and 2-hydroxyethyl methacrylate. Two separate tri-enzymatic cascade reactions were carried out. In the first cascade the enzymes β-galactosidase, glucose oxidase, and horseradish peroxidase were used and the second cascade consisted of the enzymes phospholipase D, choline oxidase, and again horseradish peroxidase. The (long-term) activity of free and hydrogel-immobilized enzymes was evaluated by UV-vis spectroscopic measurements. Additionally, time-dependent enzyme leakage from the hydrogel was investigated. Following the successful execution of multi-enzymatic reactions in bulk hydrogels, the material was integrated into PDMS-on-glass microfluidic reactors to carry out the enzyme reactions in miniaturized scale and under continuous flow. For that, hydrogel dots with a diameter of 350 μm were covalently attached to planar glass substrates by UV-initiated polymerisation of the enzyme-containing hydrogel precursor. Experiments were carried out both in channel reactors with hydrogel dots arranged in rows and wide chamber reactors with a hexagonal array of hydrogels. Especially the latter one showed a good performance as the flow velocity and thus the shear force on the hydrogel was decreased. Additionally, the residence time of the substrate and consequently the yield were increased. Long-term activity of the tri-enzymatic reactions in microfluidic reactors was proven with an ABTS assay indicating that this approach may be used as a platform for the integration of (multi-)enzymatic hydrogel dot reactions in microfluidic systems without the need of additional modification steps.
CRIS-Team Scopus Importer:2022-04-14